1998
DOI: 10.1037/0012-1649.34.4.723
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of social reputation and peer relationships in Italian children: A cross-cultural perspective.

Abstract: A group of Italian children (790 boys and 717 girls), 10-13 years old, were administered the Revised Class Play (Masten, Morison, & Pellegrini, 1985) in order to explore cross-cultural differences in social reputation with respect to North American studies. Children also were given sociometric nominations to examine the association between social reputation and peer acceptance-rejection. Exploratory and confirmatory factor analyses showed a 4-factor structure with the original Leadership-Sociability factor spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 40 publications
7
80
0
4
Order By: Relevance
“…As previously noted, in Western and individualistic cultures within which such individual characteristics as independence, assertiveness, expressiveness, and competitiveness are valued and encouraged (e.g., Argentina, Canada, Greece, Italy, the Netherlands, and the United States), shyness and social withdrawal are generally linked to peer rejection and other negative outcomes (Casiglia, Lo Coco, & Zappulla, 1998 ;Cillessen, van IJzendoorn, van Lieshout, & Hartup, 1992 ;Rubin, Chen, & Hymel, 1993 ;Schaughency, Vannatta, Langhinrichsen, & Lally, 1992 ). In contrast, in a series of studies in the 1990s, Chen and colleagues demonstrated that shyness in collectivist China was more likely to be encouraged and accepted by peers, and positively associated with social competence, peer acceptance, and academic success (e.g., Chen et al, 1995 ;Chen, Rubin, Li, & Li, 1999 ).…”
Section: Peer R Elationshipsmentioning
confidence: 98%
“…As previously noted, in Western and individualistic cultures within which such individual characteristics as independence, assertiveness, expressiveness, and competitiveness are valued and encouraged (e.g., Argentina, Canada, Greece, Italy, the Netherlands, and the United States), shyness and social withdrawal are generally linked to peer rejection and other negative outcomes (Casiglia, Lo Coco, & Zappulla, 1998 ;Cillessen, van IJzendoorn, van Lieshout, & Hartup, 1992 ;Rubin, Chen, & Hymel, 1993 ;Schaughency, Vannatta, Langhinrichsen, & Lally, 1992 ). In contrast, in a series of studies in the 1990s, Chen and colleagues demonstrated that shyness in collectivist China was more likely to be encouraged and accepted by peers, and positively associated with social competence, peer acceptance, and academic success (e.g., Chen et al, 1995 ;Chen, Rubin, Li, & Li, 1999 ).…”
Section: Peer R Elationshipsmentioning
confidence: 98%
“…(© Janet Wishnetsky /Corbis) Ähnliche kulturübergreifende Parallelen fanden sich im Hinblick auf sozialen Rückzug und soziale Ablehnung. Zum Beispiel zeigten mehrere Untersuchungen an Schulkindern in Deutschland und Italien sowie Honkong, dass genau wie in den USA Rückzug und Verschlossenheit in der Grundschule mit der Ablehnung durch die Peers verknüpft ist (Asendorpf 1990;Attili et al 1997;Casiglia et al 1998, Nelson et al 2010Schwartz et al 2010).…”
Section: Einflussfaktoren Des Peerstatus: Kulturvergleichende Aspekteunclassified
“…Studies carried out in North America found that children whose behavior was consistent with their teachers' beliefs and expectations, were rated more positively by their peers than were children whose behavior was not endorsed or was negatively viewed by teachers (Hughes, Cavell, & Wilson, 2001;La Fontana & Cillessen, 2002). Other studies have shown that children use teachers' appraisals of their classmates as a reference point for determining acceptable behavior, and then they evaluate their peers accordingly (Bierman, 2011;Casiglia, Coco, & Zappulla, 1998;La Fontana & Cillessen, 2002).…”
Section: Extending Sociometrically-derived Peer Statusesmentioning
confidence: 99%